Requirements for destination management organizations in destination governance: Understanding DMO success - Volgger, M.; Pechlaner, Harald (Pergamon Press, 2014)
In current conceptualizations of destination management, destination management organizations (DMOs) are required to act as network managers. Previous research claims that DMOs capable of actively fostering collaboration between destination stakeholders are key to ensuring a destination's competitiveness. Yet, empirical investigations concerning the role of DMO success in establishing the competitiveness of destinations are rare. Even less is known about determinants of DMO success. Therefore, the main objective of this study is to better understand DMO and destination success by investigating the role played by networking capability. One key insight is that the effect of networking capability works through increased DMO authority, i.e. enhanced power and acceptance of the DMO within the destination network. Besides the advances in terms of content, our research also offers a relevant methodological contribution by introducing a recently developed approach in mediation analysis, which has so far received little attention in the tourism literature. © 2013 Elsevier Ltd.